Capillary Hemangioma of Thoracic Spinal Cord: PET/CT and MR Findings. (May 2017) - Shen, Guohua; Su, Minggang; Zhao, Junyi; Liu, Bin; Kuang, Anren
Abstract : Abstract: Capillary hemangiomas are frequently encountered superficially in the cutaneous, subcutaneous, or mucosal tissues during the childhood and early adulthood, but the occurrence of spinal intradural capillary hemangioma is relatively rare. Herein, we report a case with capillary hemangioma of the thoracic spine. MR and PET/CT features of this lesion are presented, and awareness of this entity may help differentiate it from other spinal intradural tumors.